El tráfico de órganos en la legislación ecuatoriana y el Derecho Comparado. - Quingaluisa Sandoval, Marina Noemi (2022)
This research to look for awareness of the legal problems related to organ trafficking, legal organ trade, organ transplantation, organ donation, the rights of people who suffer from catastrophic or rare diseases, in addition to ensure the needs of users or beneficiaries of donations to make use and enjoyment of their rights, especially the right to health and life. Within the criminal law we find organ trafficking, which although it is typified in the Organic Integral Criminal Code, its opposite must be analyzed, which is organ donation, that in practice would not be carried out in a transparent manner, since the donations data should be public. In addition, to demonstrate the need that people in Ecuador have to access a donation since the issue of supply and demand of organs is becoming more and more evident. On the other hand, with the use of legal norms and doctrine, to access the background and current data on organ trafficking to ensure an adequate understanding of the subject of this research. This research also contains comparative law since it is necessary to find similarities and differences between the legal norms of the different countries to solve the problem, as well as to try to avoid legal loopholes and violations of rights.